Family history of atherosclerotic vascular disease is associated with the presence of abdominal aortic aneurysm. (February 2016) - Ye, Zi; Bailey, Kent R; Austin, Erin; Kullo, Iftikhar J
We investigated whether family history (FHx) of atherosclerotic cardiovascular disease (ASCVD) was associated with presence of abdominal aortic aneurysm (AAA). The study cohort comprised of 696 patients with AAA (70±8 years, 84% men) and 2686 controls (68±10 years, 61% men) recruited from noninvasive vascular and stress electrocardiogram (ECG) laboratories at Mayo Clinic. AAA was defined as a transverse diameter of abdominal aorta ⩾ 3 cm or history of AAA repair. Controls were not known to have AAA. FHx was defined as having at least one first-degree relative with aortic aneurysm or with onset of ASCVD (coronary, cerebral or peripheral artery disease) before age 65 years. FHx of aortic aneurysm or ASCVD were each associated with presence of AAA after adjustment for age, sex, conventional risk factors and ASCVD: adjusted odds ratios (OR; 95% confidence interval): 2.17 (1.66–2.83, p < 0.01) and 1.31 (1.08–1.59, p < 0.01), respectively. FHx of ASCVD remained associated with AAA after additional adjustment for FHx of aortic aneurysm: adjusted OR: 1.27 (1.05–1.55, p = 0.01). FHx of ASCVD in multiple arterial locations was associated with higher odds of having AAA: the adjusted odds were 1.23 times higher for each additionally affected arterial location reported in the FHx (1.08–1.40, p = 0.01). Our results suggest both unique and shared environmental and genetic factors mediating susceptibility to AAA and ASCVD.